2022
DOI: 10.3389/fmolb.2022.900433
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Gene Signature to Predict Breast Cancer Prognosis

Abstract: Background: The existing metabolic gene signatures for predicting breast cancer outcomes only focus on gene expression data without considering clinical characteristics. Therefore, this study aimed to establish a predictive risk model combining metabolic enzyme genes and clinicopathological characteristics to predict the overall survival in patients with breast cancer.Methods: Transcriptomics and corresponding clinical data for patients with breast cancer were downloaded from The Cancer Genome Atlas (TCGA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 79%
“…We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival. We found our signature have similar short-term survival (3-year) prognostic value compared with them, such as the ferroptosis-related gene signature ( Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ), pyroptosis-related gene signature ( Chen et al, 2022 ), necroptosis-related gene signature ( Yu et al, 2022 ), apoptosis-related gene signature ( Zou et al, 2022 ), zinc finger protein-related gene signature ( Ye et al, 2021 ), autophagy-related gene signature ( Lin et al, 2020 ), and metabolic-related gene signatures ( Lu et al, 2022b ). In addition, our model only involves four genes, while other models (11/13) tend to have more, which is more convenient to use to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is an out-of-control proliferation of mammary gland epithelial cells due to a variety of carcinogenic factors [12,13]. The early stage of the disease is often manifested as breast lumps, nipple discharge, axillary lymph node enlargement and other symptoms, and the late stage can be manifested as the distant metastasis of cancer cells, multiple organ lesions and the direct threat to the patient's life [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the limits of clinicopathologic characteristics, predicting the potential therapeutic genes of cancer is still difficult for many malignancies, which is important for cancer management. Identification of gene expression profiles can aid in the improvement of patient care by offering directions for individualized treatment strategies (48). Twenty-seven apoptosis-regulated genes were included for statistical comparison in the current study.…”
Section: Discussionmentioning
confidence: 99%